Pengukuran Indeks Kebersamaan Masyarakat Dalam Menghadapi Pandemi Covid-19 - Didik Setiyadi; Syahbaniar Rofiah; Jadi Suriadi (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2020)
Abstract At this time the community is being positioned with the corona virus which is not possible for activities outside the home. The role of the community is very important in these conditions, previously the community could move freely outside the house while now it can only stay at home. This study aims to determine the community togetherness index in Covid-19 by using the Wellbeing Methodology (WM) method by measuring through electronic questionnaire (EQ) with 421 respondents from 3 (three) categories namely Jakarta, Bodetabek and outside Jabodetabek. The overall assessment results show a value of 7.23 which means